Speaking skill and critical thinking skill development through project based learning method of EFL tertiary students - Sholikhah, Masriatus (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2019)
This research explored students achievement in speaking class in EFL setting by implementing project-based learning (PBL) in both their speaking skill and critical thinking skill. The research set out in two cycles of classroom action research which involved 30 students taking a compulsory subject, Speaking for Academic Setting. The researcher utilized some instruments to obtain valid data with observation and consultation sheets, peer assessment, deep interview, and Questionnaire. The students are given some set of projects in producing Vlog then uploaded it in YouTube platform. They have to work in a small group (3 person) and pretend to be a news anchor, news reporter, host in TV program, and personal vlog consecutively. The result showed that PBL significantly elevates students‘ speaking skill as well as critical thinking skill for they enjoyed their self pretending as an “artist“ and actively engaged in the process of discussion, sharing, and cooperate among group member.